Os bancos comunitários e o empoderamento dos clientes? Avaliação da experiência do Crediamigo do Banco do Nordeste - Leandro, Charles Diniz (2009)
The objective of this paper is to evaluate the experience of Banco do Nordeste’s Crediamigo program enhancing the methodology used in communal banks and its approach in addressing the issue of empowerment. To this end, the historical and political context in which the Banco do Nordeste do Brasil, its microfinance department and its Microcredit Program – Crediamigo were founded is examined. After which, the genesis and the trajectory of Crediamigo Comunidade during the period from August 2004 to December 2008 is presented and comments on the political and institutional context inherent in this product. Within this context enters a discussion of empowerment, comparing this concept with the characteristics present in the methodology of Crediamigo Comunidade. The third part of this document describes the socioeconomic profile of the public being served by this product and their perception of Crediamigo Comunidade which was gathered through interviews with these clients and an analysis of the data that was gathered in these interviews. This paper ends by identifying the limits and possibilities of social programs and microfinance public policy, empirically examining the horizons of empowering the poor communities served by Crediamigo.